Community engagement and human perception in crocodile conservation: preliminary steps in Sian Ka’an Biosphere Reserve - Benítez-Moreno, Javier Arturo; Cedeño-Vázquez, José Rogelio; Castelblanco-Martínez, Delma Nataly (Frontiers in Conservation Science, 2024)
Introduction Wildlife tourism is important for the conservation of protected areas, endangered species, and to empower local communities. Nevertheless, when guidelines and practices are not clear and correctly executed, tourism may have a negative impact. Methods We carried out semi-open interviews (n = 34) and several workshops (n = 50) with locals and tour guides in the village of Punta Allen in Sian Ka'an Biosphere Reserve, Mexico. Data were organized in tables in Excel®, and statistical analysis was conducted with IBM® SPSS® Statistics software. A priori, exploratory data analysis was carried out to identify the general pattern of the data, and a priori data normality test (Shapiro–Wilks) and χ2 test were carried out to find out if there were differences in the frequency of a response depending on socioeconomic variables. Results Most respondents (69%) dedicated 2–10 min to crocodile observation, one quarter (25%) spent 11–20 min, and the remainder (6%) 21–30 min. The majority (97%) of respondents mentioned that when they see a crocodile, they approach at a 5–10 m distance and wait for the occupants of the boat to take pictures, and then leave; only one respondent (3%) said that they feed crocodiles to attract them to the boat. Most respondents (89%) said that crocodile observation does not need to be improved, and it is fine the way it is currently carried out; the remaining 11% said that it could be improved. Workshops were received positively and allowed us to share information on crocodile species, their conservation, and good tourism practices. Discussion It is necessary to enlighten tourism service providers about the biology and importance of crocodilian species, to promote conservation and provide services with an educational impact/focus for visitors to the reserve. There is a need to develop a communication program that provides accurate information for new service providers and renews and reinforces concepts for established providers. Additionally, we need to continuously monitor and evaluate wildlife observation activities to enhance current practices in our study area, and to determine if they are having a negative impact on crocodile behavior and biology.